CAR T-cell therapy for B-cell lymphomas: clinical trial results of available products. (April 2019) - Chavez, Julio C.; Bachmeier, Christina; Kharfan-Dabaja, Mohamed A.
Adoptive cellular immunotherapy with chimeric antigen receptor (CAR) T cell has changed the treatment landscape of B-cell non-Hodgkin's lymphoma (NHL), especially for aggressive B-cell lymphomas. Single-center and multicenter clinical trials with anti-CD19 CAR T-cell therapy have shown great activity and long-term remissions in poor-risk diffuse large B-cell lymphoma (DLBCL) when no other effective treatment options are available. Two CAR T-cell products [axicabtagene ciloleucel (axi-cel) and tisagenlecleucel] have obtained US Food and Drug Administration approval for the treatment of refractory DLBCL after two lines of therapy. A third product, liso-cel, is currently being evaluated in clinical trials and preliminary results appear very promising. CAR T-cell-related toxicity with cytokine-release syndrome and neurotoxicity remain important potential complications of this therapy. Here, we review the s biology, structure, clinical trial results and toxicity of two commercially approved CAR T-cell products and others currently being studied in multicenter clinical trials in B-cell NHLs.